A new risk locus in CHCHD5 for hypertension and obesity in a Chinese child population: a cohort study. Issue 9 (11th September 2017) - Wu, Lijun; Gao, Liwang; Zhao, Xiaoyuan; Zhang, Meixian; Wu, Jianxin; Mi, Jie
Abstract : Objective: Coiled-coil-helix-coiled-coil-helix domain containing 5 (CHCHD5), a mitochondrial protein, is involved in the oxidative folding process in the mitochondrial intermembrane space. A previous study identified a hypertension-related single nucleotide polymorphism (SNP), rs3748024, in CHCHD5 in adults, but there are no reports regarding the association between CHCHD5 and obesity, which is a known risk factor for hypertension. The aim of the present study is to investigate the associations of the SNP rs3748024 with hypertension and obesity. Design: Cohort study. Setting: Institute of Pediatrics in China. Participants: We genotyped the SNP rs3748024 in the Beijing Child and Adolescent Metabolic Syndrome study. A total of 3503 children participated in the study. Primary and secondary outcome measures: Genotyping of rs3748024 was conducted using the TaqMan Allelic Discrimination Assay. Lipids and glucose were analysed by an automatic biochemical analyser using a kit assay. The levels of adipocytokines (leptin, adiponectin and resistin) were measured by ELISA techniques. Results: There was a statistically significant association between rs3748024 and systolic blood pressure (SBP) (β=−0.853, 95% CI −1.482 to −0.024, p=0.044) under an additive model adjusted for age, gender and body mass index (BMI) after correction for multiple testing. The SNP was also significantly associated with BMI (β=−0.286, 95% CI −0.551 to −0.021, p=0.043), obesity (OR=0.828, 95% CI 0.723 to 0.949, p=0.018) and triglycerides (β=−0.039, 95% CI −0.070 to −0.007, p=0.044) after correction for multiple testing. Conclusions: We demonstrate for the first time that the SNP rs3748024 in CHCHD5 is associated with SBP, BMI, obesity and triglycerides in Chinese children. Our study identifies a new risk locus for hypertension and obesity in a child population. The function of CHCHD5 remains to be further studied to help elucidate the pathogenic role of CHCHD5 in hypertension and obesity.